Tinjauan Hukum dan Upaya Pencegahan terhadap Kasus Kebocoran Data NPWP - Hizkia Roland Prawyra Sitorus; Dewi Pika Lumbanbatu; Daniel David Sidebang; Dules Ery Pratama; Risky Sakti Lumban Gaol (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Taxpayer User Number (NPWP) data is something private to be published or known by everyone. Based on Law Number 27 of 2022, the contents of the Law are concerning Personal Data Protection (PDP). This law regulates the protection of citizens' personal data, including the rights of data owners, data controller obligations, and sanctions for violations. Today, adults are uncovering the Bjorka case that published several other people's NPWP data which made all NPWP users afraid. Therefore, this journal discusses the Legal Review and Prevention Efforts for NPWP Data Leakage Cases. This research was conducted using a qualitative descriptive research method through a literature study approach.